2009
DOI: 10.1158/1940-6207.capr-08-0201
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Oral Anthocyanins for Colorectal Cancer Chemoprevention

Abstract: Naturally occurring anthocyanins possess colorectal cancer chemopreventive properties in rodent models. We investigated whether mirtocyan, an anthocyanin-rich standardized bilberry extract, causes pharmacodynamic changes consistent with chemopreventive efficacy and generates measurable levels of anthocyanins in blood, urine, and target tissue. Twenty-five colorectal cancer patients scheduled to undergo resection of primary tumor or liver metastases received mirtocyan 1.4, 2.8, or 5.6 grams (containing 0.5-2.0 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 28 publications
(38 reference statements)
0
77
0
3
Order By: Relevance
“…Repeated consumption of fruits and vegetables containing high levels of anthocyanins reduces the risk of tumor development in breast and colon cancers. In addition, anthocyanin intake inhibits tumor proliferation in patients with colorectal cancer (6,10). Studies have also indicated that various anthocyanins derived from fruits and vegetables are effective in the prevention or reduction of solid tumor development in animal models (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Repeated consumption of fruits and vegetables containing high levels of anthocyanins reduces the risk of tumor development in breast and colon cancers. In addition, anthocyanin intake inhibits tumor proliferation in patients with colorectal cancer (6,10). Studies have also indicated that various anthocyanins derived from fruits and vegetables are effective in the prevention or reduction of solid tumor development in animal models (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…This autophagy-inducing activity of ATCs could explain the chemopreventive effect of ATCs reported in the esophagus and the colon (11,12), although the autophagyinducing activity of ATCs in non-transformed cells remains to be determined. A metabolic shift to aerobic glycolysis has generally been regarded as a driving force for carcinogenesis (35,36), and dysregulated metabolic homeostasis and obesity have been reported to increase the risk of certain types of cancer, such as breast cancer (37).…”
Section: Discussionmentioning
confidence: 96%
“…This anti-inflammatory activity of ATCs was shown to be effective in vivo to subside circulatory and multiple organ failures due to endotoxemia (8). Based on these apoptosis-inducing and anti-inflammatory as well as anti-invasive and anti-angiogenic effects (9,10), attempts have been made to develop ATCs as a chemopreventive agent, and promising results of pilot studies in rodent models of esophageal and colorectal cancers and human colorectal cancer patients have provided support for this hypothesis (11,12). In addition to inducing apoptosis, it has been suggested that ATCs induce autophagy in cancer and glial cells (13,14), although the mechanism for this remains to be clarified.…”
Section: Anthocyanins In the Black Soybean (Glycine Max L) Protect Umentioning
confidence: 99%
“…However, in the absence of a zero dose control group, authors couldn't determine if this increase could, at least, to some extent, be the consequence of inherent procedural differences in measurements. Nevertheless, the pharmacodynamic changes observed seemed to be more prominent in patients at a dose of anthocyanins, which elicited target tissue levels below the detection limit, than at higher one, which furnished detectable anthocyanin levels in colorectal tissue (Thomasset et al, 2009). However, an Italian study aimed at investigating the relationship between anthocyanidins intake and risk for oral or pharyngeal cancer did not show any significant association (Rossi et al, 2007).…”
Section: Cytotoxicity In Colon and Other Cancer Cell Linesmentioning
confidence: 98%